Efficacy of Low-Dose Rituximab on Neuromyelitis Optica-Associated Optic Neuritis - Zhao, Shuo; Zhou, Huanfen; Xu, Quangang; Dai, Hong; Wei, Shihui (Frontiers in Neurology, 2021)
Purpose: To prospectively investigate the efficacy and tolerance of low-dose rituximab (RTX) for the treatment of neuromyelitis optica-associated optic neuritis (NMO-ON). Methods: ON patients with seropositive aquaporin 4-antibody (AQP4-Ab) were diagnosed with NMO-ON and recruited for treatment with low-dose RTX (100 mg*4 infusions) and were then followed monthly for a minimum of 3 months. Reinfusion of 100 mg RTX was given when the CD19+ B lymphocyte frequency was elevated to above 1%. The serum AQP4-Ab level was tested by an enzyme-linked immunosorbent assay (ELISA). Results: A total of 43 NMO-ON patients (1 male/42 female, 75 involved eyes) were included in this study. CD19+ B cell clearance in the peripheral blood was induced in 97.7% of patients after induction treatment. A significant decrease in serum AQP4-Ab concentration was observed after induction treatment (P=0.0123). The maintenance time of B cell clearance was 5.2±2.25 months. The relapse-free rate was 92.3% in patients followed-up for over 12 months, and patients with nonorgan-specific autoimmune antibodies tended to relapse within 6 months. A total of 96.2% of patients had stable or improved vision, and a decrease in the average EDSS score was found. Structural alterations revealed by optic coherence tomography were observed in both ON and unaffected eyes. The rates of infusion-related reactions and long-term adverse events were 18.6% and 23.1%, respectively. No severe AEs was observed. Conclusions: Low-dose rituximab is efficient and well tolerated in treating NMO-ON.